Surveilans Penyalahgunaan Bahan Kimia Sintetis Deksametason Pada Jamu Pegal Linu Menggunakan Metode Near Infra Red dan Kemometrik - Khrisna Agung Cendekiawan; Sugeng Winarso; Ancah Caesarina Novi Marchianti (Multidisciplinary Journal, 2019)
Law Number 36 of 2009 regarding Health states that the community is given the widest opportunity to process, produce, distribute, develop, improve, and use traditional medicines that can be justified for their benefits and safety. The presence of medicinal chemicals added to traditional medicines (herbs) is not appropriate to the therapeutic dose, resulting in overdosing and causing side effects that can be harmful to the health of the consumers. One of the analytical methods to detect the presence of medicinal chemicals, especially dexamethasone, is the Near Infra Red and Chemometrics method. The research design used in this study was descriptive non-analytic. The population in this study is 28 herbal medicine shop that sells herbal sore-aches traditional medicines (jamu pegal linu) in Jember Regency using the Total Sampling technique. This study is using univariate analysis of frequency distribution. This research shows that there was no chemical content of dexametasone found in all herbal medicine samples in the analysis using the Near Infra Red method while in the Chemometric testing, it was found that one of the herbal samples (code J-C) contained 2% of dexamethasone. It is imperative to Socialize to the community the impact of using herbal medicine containing medicinal chemicals, and it also needs to be analyzed using the most sensitive methods.Keyword: Chemical Abuse, Dexamethasone, Sciatica Herbs, Near Infra Red, Chemometric Methods